A meta-analysis of randomized controlled trials of uninterrupted periprocedural anticoagulation strategy in patients undergoing atrial fibrillation catheter ablation. (1st November 2018) - Zhao, Yating; Lu, Yao; Qin, Yue
Abstract: Background: In patients undergoing atrial fibrillation (AF) ablation, despite uninterrupted oral anticoagulants (OACs) have been recommended, no consensus has emerged regarding to whether uninterrupted novel oral anticoagulants (NOACs) are superior to uninterrupted vitamin K antagonists (VKAs) for the periprocedural antithrombotic management. This meta-analysis aimed to compare the efficacy and safety of uninterrupted NOACs and uninterrupted VKAs in patients undergoing AF ablation. Methods: Databases were searched for articles published up to March 20, 2018. Only randomized controlled trials (RCTs) were selected. The data were analyzed with RevMan 5.3 using a fixed-effects method. Results: 6 RCTs and 1903 patients were included. There was no significant difference between NOACs group and VKAs group in incidence of stroke or TIA (OR = 1.00, 95% CI = 0.23–4.40, P = 1.00), silent cerebral thromboembolic events (OR = 1.09, 95% CI = 0.67–1.75, P = 0.74) or minor bleeding (OR = 1.01, 95% CI = 0.78–1.31, P = 0.93), which were consistent in subgroup analysis of individual NOAC vs. VKAs group. NOACs treatment was associated with reduced risk of major bleeding as compared with VKAs (OR = 0.45, 95% CI = 0.26–0.81, P < 0.01). In the subgroup analyses, only the dabigatran group showed significant lower incidence of major bleeding compared to VKAs group. Conclusions: In patients undergoing AF ablation, uninterrupted NOACs is as effective as uninterrupted VKAs treatment, uninterrupted dabigatran (150 mg twice daily) may be superior to other uninterrupted OACs strategies. Highlights: Uninterrupted NOACs is as effective as uninterrupted VKAs in patients undergoing AF ablation. Uninterrupted dabigatran may be the safest for periprocedural anticoagulation management. Optimal strategy for periprocedural anticoagulation management remains to be determined.